Cumplimiento de las normas de bioseguridad en laboratorios de la Universidad Técnica de Machala - Hurtado Zapata, Andrea del Rocío; Santos Luna, Jovanny Angelina; Manzanares Loaiza, Silvana Gabriela; Machuca Loja, Geanina Jacqueline (My University, 2021)
Objective: To establish compliance with Biosafety standards by professionals working in the laboratories of the Faculty of Chemistry and Health Sciences of the Technical University of Machala. Materials and Methods: This is a descriptive research with a quantitative approach. The modality of the research is field research. The population consisted of 100 students who use the different laboratories of the Faculty of Chemistry and Health Sciences of the Technical University of Machala. Results: 59% of the population answered that they had received training on Biosafety norms in the institution and 41% answered that they had not. Seventy-three percent of the students comply with Biosafety measures in the laboratory. Hand washing is performed, with an equivalent of 39% for after having contact with any type of materials, biological samples, solid products, substances or reagents. Regarding whether there are disposal containers for contaminated items, and whether they are properly identified, this corresponds to 46.9%. To the question about what materials are deposited in the guards giving an equivalent of 43% for syringes, scapel powever, Lancets, needles. Conclusions: It could be determined that the great part of the population studied if they comply with Biosafety standards
Objetivo: Establecer el cumplimiento de las normas de bioseguridad por parte de los profesionales que laboran en los laboratorios de la Facultad de Ciencias Químicas y de la Salud de la Universidad Técnica de Machala. Materiales y Métodos: La presente investigación es de tipo descriptiva, con enfoque cuantitativo. La modalidad de la investigación es de campo. La población estuvo constituida por 100 estudiantes que usan los diferentes laboratorios de la Facultad de Ciencias Químicas y de la Salud de la Universidad Técnica de Machala. Resultados: El 59% de la población contestó que sí, ha recibido capacitación acerca de las normas de bioseguridad en la institución y el 41% respondieron que no. El 73% de los estudiantes cumplen con las medidas de bioseguridad en el laboratorio. Se realiza el lavado de manos, con un equivalente a un 39% para Después de tener contacto con cualquier tipo de materiales, muestras biológicas, productos sólidos, sustancias o reactivos. Sobre si se cuentan con recipientes de descarte para elementos contaminados, y están debidamente identificados el cual corresponde a un 46,9%. A la pregunta sobre qué materiales se deposita en los guardianes dando un equivalente de 43% para las Jeringuillas, bisturí, sin embargo, las Lancetas, agujas. Conclusiones: Se pudo determinar que la gran parte de la población estudiada si cumplen con las normas de bioseguridad.
Keywords: NORMAS DE BIOSEGURIDAD; LABORATORIOS; UNIVERSIDAD TECNICA DE MACHALA.